Challenging Atroposelective C–H Arylation - Wencel-Delord, Joanna; Colobert, Françoise (SynOpen, 2020)
Atropisomeric molecules are privileged scaffolds, not only as ligands for asymmetric synthesis, but also as biologically active products and advanced materials. Although very attractive from a sustainability viewpoint, the direct construction of the stereogenic axis through asymmetric C–H arylation is very challenging and consequently only a few examples have been reported. This short review summarizes these very recent results on the atropo-enantio or diastereoselective synthesis of atropisomeric (hetero)biaryl molecules; transformations during which the Ar–Ar atropisomeric axis is formed during the C–H activation process.1 Introduction2 Atropo-enantioselective Intermolecular Pd-Catalyzed C–H Arylation of Thiophene Derivatives3 Atropodiastereoselective Intermolecular Pd-Catalyzed C–H Arylation towards Terphenyl Scaffolds Bearing Two Atropisomeric Axes4 Atropo-enantioselective Intramolecular Pd-Catalyzed C–H Arylation towards Atropisomeric Benzodiazepinones5 Atropo-enantioselective Intermolecular Pd-Catalyzed C–H Arylation of Heteroarenes6 Rh-Catalyzed Atropo-enantioselective C–H Arylation of Diazonaphthoquinones7 Conclusion
Keywords: atropisomeric axis; atropisomeric biaryls; C–H arylation